2015
DOI: 10.1055/s-0035-1546214
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Characterization of Intravenous and Oral Pharmacokinetics of Lychnopholide in Rats by Transit Compartment Model

Abstract: The pharmacokinetic properties of a new molecular entity are important aspects in evaluating the viability of the compound as a pharmacological agent. The sesquiterpene lactone lychnopholide exhibits important biological activities. The objective of this study was to characterize the pharmacokinetics of lychnopholide after intravenous administration of 1.65 mg/kg (n = 5) and oral administration of 3.3 mg/kg (n = 3) lychnopholide in rats (0.2 ± 0.02 kg in weight) through nonlinear mixed effects modeling and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…To our knowledge, this is the first time an LC‐MS/MS method was developed to quantify LYC in the plasma. The method presented here is suitable for pharmacokinetics studies and allowed us to determine the noncompartmental and compartmental pharmacokinetc parameters of LYC by simultaneously modelling the concentration–time profiles after both oral and intravenous administrations of LYC (Lachi‐Silva et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…To our knowledge, this is the first time an LC‐MS/MS method was developed to quantify LYC in the plasma. The method presented here is suitable for pharmacokinetics studies and allowed us to determine the noncompartmental and compartmental pharmacokinetc parameters of LYC by simultaneously modelling the concentration–time profiles after both oral and intravenous administrations of LYC (Lachi‐Silva et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…In the same study, the protein binding was determined as ~99% in rat total plasma for three different concentrations of LYC (Lachi‐Silva et al ., ). The high protein binding of LYC is probably the cause for the low average recovery rate, as the liquid–liquid extraction may not have extracted the compound thoroughly in the sample.…”
Section: Resultsmentioning
confidence: 97%
“…A recent study with rats suggested the favorable use of oral LYC as an active substance or pharmacological agent because of its physicochemical properties of good permeability and rapid absorption, distribution, and elimination, resulting in 68% oral bioavailability (21). However, LYC has poor solubility, and its fast elimination implies its possible administration in repeated doses.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that LYC administered orally to rats showed suitable pharmacokinetic characteristics (21). Oral administration is the preferred route for the treatment of parasitic diseases, including CD.…”
mentioning
confidence: 99%
“…12% in PBS/Tween 8 ), probably because proteins act as LYC acceptors favouring LYC partition to the external aqueous medium from the triglyceride-based core of the NC. The main driving force is probably the LYC strong binding to mouse plasma proteins as recently reported with rat plasma 25 . This accelerating effect of plasma proteins on the release of a lipophilic drug has already been observed with similar PLA-PEG NC 26 , 27 .…”
Section: Discussionmentioning
confidence: 57%